Vpliv fizioloških dražljajev in nevrohumoralni odzivi pri preddvornoprekatni in sinhroni prekatni elektrostimulaciji srca - Žižek, David (Zdravniški vestnik, 2005)
Background. VDD pacing system is an alternative to DDD pacing system. Due to different fixation of electrodes in both systems, detected of atrial signal many vary greatly and can be influenced by posture and exercise. Inappropriateatrial sensing leads into loss of atrioventricular synchrony. Haemodynamic changes that occur have a distinctive influence on peripheral levels ANP and BNP. Methods. Our prospective study encompassed seventy-five patients with implanted VDD or DDD pacing system in year 2000. Using the programmer we directly measured sensing threshold in atrium supine, sitting upright and after standardized exercise. Among measured data we evaluated AV synchrony. Blood was collected from an antecubital vein and plasma proANP and NT-proBNP levels were measured. Results. Atrial sensing was significantly lower with VDD compared to DDD (p<0.001). The difference between supine and sitting upright among each pacing system was not significant (p=0.82). Atrial sensing was significantly lower after exercise compared to supine with VDD (p<0.05). VDD AV synchrony was lower (p<0.001). Difference of ANP levels was not significant (p=0.13). Levels of BNP were lower with VDD (p<0.05). Levels of ANP, BNP are negatively correlated to AV synchrony (o=-0.44, p<0.001 and o=-0.54, p<0.001, respectively). Levels of BNP and ANP are closely correlated (o=0.71, p<0,001). Conclusions. Posture did not have any significant effect onatrial sensing. However, in VDD pacing system atrial sensing was affected byexercise. Lower AV synchrony with VDD pacing system suggests lower haemodynamic support. Peripheral levels of natriuretic peptides were associated with AV synchrony. Therefore, haemodynamic affect can be predicted by measuring peripheral levels of either ANP or BNP.
Keywords: Atrial Natriuretic Factor; Cardiac Pacing, Artificial; Electrodes, Implanted; Elektrode implantirane; Exercise; Heart Atrium; Methods; Preddvorni, natriuretični faktor; Prospective Studies; Prospektivne študije; Srce, predvor; Srčno vzpodbujanje, umetno; Telesna vadba